El cerro de Alarcos (Ciudad Real) Formación y desarrollo de un oppidum ibérico : 20 años de excavaciones arqueológicas en el Sector III - del Rosario García Huerta, María (Archaeopress Publishing, 2020)
El cerro de Alarcos (Ciudad Real): Formación y desarrollo de un oppidum ibérico presents the results of archaeological work which has been carried out since 1997 in so-called Sector III of the Alarcos site, located on a hill next to the Guadiana river, a few kilometres from Ciudad Real. These archaeological campaigns have made it possible to obtain essential information to understand the communities that, from the end of the Bronze Age to the end of the Iron Age, inhabited this large town and its surrounding area.An interesting set of structures and other evidence of material culture have been recovered, which allow us to characterize the daily activities of people between the 10th-11th century BC and, in addition, they enable us to understand the paleoenvironment of this territory and the nature of the economy and the food transformation activities of these protohistoric populations.The use of this territory has been determined over the centuries, being originally a residential area which later, in Iberian times, assumed economic functionality, as it was intended for grain storage, grinding and cooking food.The documentation of a wide and varied repertoire of ceramic materials and an interesting set of foreign ceramics corroborates the dynamism this settlement achieved, during both the Pre-Iberian period and the full Iberian period.